Analisis Pengaruh Customer Relationship Management (CRM) Terhadap Customer Satisfaction dan Customer Loyalty : Studi Pada Pengguna Dompet Digital Go-Pay Di Pekalongan - Laelatul Maulida; Wenti Ayu Sunarjo; Rengga Kusuma Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of Customer Relationship Management (CRM) on Customer Satisfaction and Customer Loyalty on the Gopay e-wallet in Pekalongan and its surroundings. This type of research is quantitative with a purposive sampling technique using a questionnaire distributed to 50 Gopay users in Pekalongan and surrounding areas. This research uses multiple regression analysis methods, classical assumption tests, t tests, and R2 square tests, using SPSS V.20. Partial test results show that Customer Relationship Management has a positive and significant effect On Customer Satisfaction and Customer Loyalty.